PENGARUH ARUS KAS TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDATAR DI BEI - Amanda Agustia Pasaribu; Nilawati Nasti; Mas’ut .; Shofwan Andri (Universitas Islam Islam Sumatera Utara, 2021)
This study aims to the effect of cash flow on stock prices in food beverage sub-sectorMaufacturing Companies listed on the Indonesia Stock Exchange. This study has a population of 21 companies that are Food and Beverage Sub Sector Manufacturing Companies listed on the Indonesia Stock Exchange during 2018-2020 which are then determined to be sampled using a purposive sampling method to obtain a sample of 13 Food and Beverage Sub Sector Manufacturing Companies by Specified criteria. The analytical method used is quantitative descriptive. Data analysis includes data feasibility test, regression analysis, and hypothesis testing partially and simultaneously. The result of this study indicate that (1) Operating Cash Flow has no effect on stock prices, (2) Investment Cash Flow has no effect on stock prices, (3) Funding cash flow has a significant effect on stock prices, (4) the effect operating cash flow, investment cash flow, and funding cash flow has no effect on stock prices.